2018
DOI: 10.1155/2018/3121604
|View full text |Cite
|
Sign up to set email alerts
|

Soil-Rock Slope Stability Analysis by Considering the Nonuniformity of Rocks

Abstract: Soil-rock slopes are widely distributed around the world, while the commonly adopted method by simplifying it as a uniform media tends to be excessively conservative. In this study, a slope stability analysis method considering the nonuniform characteristics of rocks was proposed. It was found that the distribution, relative position, and shape of rock have significant effect on slope stability. For the influence of distribution, large rocks at the foot of slope have the most significant effect on slope stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Clay-gravel mixtures (CGMs) constitute a great engineering material, which is widely utilized in subgrade engineering, rock-fill dams, and sea filling [1][2][3][4]. A CGM is a heterogeneous two-phase material, consisting of low-strength clay and high-strength and large-sized gravels.…”
Section: Introductionmentioning
confidence: 99%
“…Clay-gravel mixtures (CGMs) constitute a great engineering material, which is widely utilized in subgrade engineering, rock-fill dams, and sea filling [1][2][3][4]. A CGM is a heterogeneous two-phase material, consisting of low-strength clay and high-strength and large-sized gravels.…”
Section: Introductionmentioning
confidence: 99%
“…Soil-rock slopes, consisting of soil and rocks, are extremely heterogeneous slopes that are usually distributed in quaternary loose accumulation layers and mainly formed by residual weathering, landslides, flood alluvium, and so on [1][2][3]. The great difference between soil and rocks in strength and particle size leads to different mechanical properties in soil-rock mixtures [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15]. Liu et al [3,16] combined random establishment method of rock contours and Finite Element Methods, studied the effect of regular rock distribution to the slope stability, and concluded that the stability of a soil-rock slope improves with the increase of rock contents, and the increasing amplitude is highly related to rock distribution characteristics in slopes. In addition, Liu et al [17] adopted a two-phase medium that soil and rocks were considered to have different undrained shear strength to study the stability of a soil-rock slope by FEM and found that the slope obtains the maximum and minimum safety factor when the rocks' long axis is vertical and parallel to the slope surface, respectively, in which the minimum safety factor is always larger than the uniform soil slope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common practice is to employ either 1D or 2D measurements, or both (Sonmez et al 2004). Many investigators resolved to use aerial fractions of outcrops (2D surfaces), augmented with field and laboratory tests to obtain the geometric information of bimrock/bimsoil from outcrops (Medley 1994;Xu et al 2008Xu et al , 2011Coli et al 2012;Kahraman et al 2015;Ymeti et al 2017;Liu et al 2018;Meng et al 2018;Yang et al 2019). However, it is not always possible to obtain areal fraction of blocks through image analysis if the blocks are dyed by matrix or the chromatism between blocks and matrix is small.…”
Section: Introductionmentioning
confidence: 99%